Phytochemical Profile and Biological Activity of the Ethanol Extracts from the Aerial Parts of Adonis tianschanica (Adolf.) Lipsch. Growing in Kazakhstan - Saule Orynbekova; Wirginia Kukula-Koch; Zuriyadda Sakipova; Bashaer Alsharif; Beibhinn Rafferty; Talgat Nurgozhin; Zoya Allambergenova; Piotr Dreher; Kazimierz Głowniak; Fabio Boylan (Molecules)
Adonis tianschanica is a lesser-known plant species belonging to the genus Adonis that grows in Kazakhstan. The aim of this study was to characterize the composition of the ethanolic, water, and hydroethanolic extracts from the aerial parts of A. tianschanica by HPLC-ESI-QTOF-MS/MS to isolate the major compound isoquercitrin by HSCCC (High-Speed Counter-Current Chromatography) and to determine the cytotoxicity and anti-inflammatory potential of the extracts produced with this plant. Fingerprinting of the analyzed extracts showed the presence of a multitude of metabolites comprising polyphenols, organic acids, and coumarins, and only trace quantities of cardiac glycosides in the analyzed samples. Flavonoids were certainly the best-represented group, with kaempferol, quercetin, and their derivatives as the major components of the extracts. Key findings in this paper were that the ethanol: water (50:50 v/v) extract of A. tianschanica and its major compound isoquercitrin were able to reduce the production of NO induced by LPS, in addition to demonstrating anti-inflammatory effects by reducing cytokines such as IL-6, TNF-α, and IL-1β.